2016
DOI: 10.1007/s10389-016-0716-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of health care professionals towards Mutual Health Organizations: evidence from two regions in the Northwest Province of Cameroon

Abstract: Aim Mutual Health Organizations (MHOs) can be a potential means to reduce barriers to health care in low-income countries with poor access to health care and high health care costs for the population. One important challenge is the relationship between MHOs and health care professionals (HCPs). Our study evaluates HCPs experiences of, and attitudes towards MHOs. Subjects and Methods A total of 210 HCPs from three private and two public clinics in Kumbo and Bamenda (Cameroon) were interviewed with a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…While rich households in sub-Saharan Africa are usually able to afford the cost of healthcare out-of-pocket, the reverse happens among those in poor wealth quintiles who can even hardly afford what to eat much more to talk of health care utilisation out-of-pocket, especially for the prevention of ALRIs among children under-five (Nicholas, Edward, & Bernardin, 2016). Even though social health interventions implemented by many of the countries in the sub-region are pro-poor and meant to bridge the gap in access to and utilisation of health care including immunisation for children between the rich and poor (Haile, Ololo, & Megersa, 2014), studies have shown that it is rather the rich who end up benefiting from such interventions to the detriment of the poor (Hammer-Fomuki, Okwen, Ranft, Gardemann, & Schikowski, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While rich households in sub-Saharan Africa are usually able to afford the cost of healthcare out-of-pocket, the reverse happens among those in poor wealth quintiles who can even hardly afford what to eat much more to talk of health care utilisation out-of-pocket, especially for the prevention of ALRIs among children under-five (Nicholas, Edward, & Bernardin, 2016). Even though social health interventions implemented by many of the countries in the sub-region are pro-poor and meant to bridge the gap in access to and utilisation of health care including immunisation for children between the rich and poor (Haile, Ololo, & Megersa, 2014), studies have shown that it is rather the rich who end up benefiting from such interventions to the detriment of the poor (Hammer-Fomuki, Okwen, Ranft, Gardemann, & Schikowski, 2016).…”
Section: Discussionmentioning
confidence: 99%
“… 41 - 43 Research evidence have shown that rich people in the society tend to profit more from such intervention strategies at the expense of the poor people of the society who may actually be the targeted population for the interventions. 44 Globally, inadequate living conditions pose a high-risk factor for negative health condition and are linked to insufficient use of primary health care. 45 In some countries, several measures have been implemented to overwhelmed blockades to proper housing situations, 46 , 47 including affordable housing programs and steps to increase system quality among some of the underprivileged through a health insurance scheme that is nationally based 48 and community-based crisis intervention of illnesses that are prominent among children who are less than 5 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The following reasons for exclusion were included: 11 articles were not related to strategic health purchasing and 5 were not from Cameroon. Finally, after this second screening stage, we retained 35 articles for data extraction (Figure 1), including publications on mutual health organization (MHO) scheme, [37][38][39][40][41][42][43][44][45][46][47][48][49][50] PBF scheme, 33,34,[51][52][53][54][55][56][57][58][59][60] voucher scheme, 61 national health insurance (NHI) scheme, 36,62 private health insurance (PHI) scheme, 63 and multiple schemes [64][65][66][67][68] (Annex 1). The articles were screened using both the title and the abstract.…”
Section: The Selection Of the Studiesmentioning
confidence: 99%